Variation in SARS-CoV-2 seroprevalence across districts, schools and classes: baseline measurements from a cohort of primary and secondary school children in Switzerland - Ulyte, Agne (BMJ Open, 2021)
OBJECTIVES: To determine the variation in SARS-CoV-2 seroprevalence in school children and the relationship with self-reported symptoms. DESIGN: Baseline measurements of a longitudinal cohort study (Ciao Corona) from June to July 2020. SETTING: 55 schools stratified by district in the canton of Zurich, Switzerland. PARTICIPANTS: 2585 children (1339 girls; median age: 11 years, age range: 6–16 years), attending grades 1–2, 4–5 and 7–8. MAIN OUTCOME MEASURES: Variation in seroprevalence of SARS-CoV-2 in children across 12 cantonal districts, schools and grades, assessed using Luminex-based test of four epitopes for IgG, IgA and IgM (Antibody Coronavirus Assay, ABCORA 2.0). Clustering of cases within classes. Association of seropositivity and symptoms. Comparison with seroprevalence in adult population, assessed using Luminex-based test of IgG and IgA (Sensitive Anti-SARS-CoV-2 Spike Trimer Immunoglobulin Serological test). RESULTS: Overall seroprevalence was 2.8% (95% CI 1.5% to 4.1%), ranging from 1.0% to 4.5% across districts. Seroprevalence in grades 1–2 was 3.8% (95% CI 2.0% to 6.1%), in grades 4–5 was 2.4% (95% CI 1.1% to 4.2%) and in grades 7–8 was 1.5% (95% CI 0.5% to 3.0%). At least one seropositive child was present in 36 of 55 (65%) schools and in 44 (34%) of 131 classes where ≥5 children and ≥50% of children within the class were tested. 73% of children reported COVID-19-compatible symptoms since January 2020, with the same frequency in seropositive and seronegative children for all symptoms. Seroprevalence of children and adults was similar (3.2%, 95% credible interval (CrI) 1.7% to 5.0% vs 3.6%, 95% CrI 1.7% to 5.4%). The ratio of confirmed SARS-CoV-2 cumulative incidence-to-seropositive cases was 1:89 in children and 1:12 in adults. CONCLUSIONS: SARS-CoV-2 seroprevalence was low in children and similar to that in adults by the end of June 2020. Very low ratio of diagnosed-to-seropositive children was observed. We did not detect clustering of SARS-CoV-2-seropositive children within classes, but the follow-up of this study will shed more light on transmission within schools. TRIAL REGISTRATION NUMBER: NCT04448717.